WONKA and OOMMPPAA – analysis of protein-ligand interaction data to direct Structure Based Drug Design - Deane, C; Marsden, B; Wall, I; Green, D; Bradley, A (International Union of Crystallography, 2017)
In this work we describe two freely available web-based interactive computational tools that facilitate the analysis and interpretation of protein-ligand interaction data. First, WONKA which assists in uncovering interesting and unusual features (e.g. residue motions) within ensembles of protein-ligand structures and enables facile sharing of observations between scientists. Second, OOMMPPAA which incorporates protein-ligand activity data with protein-ligand structural data using 3D matched molecular pairs. OOMMPPAA highlights nuanced structure activity relationships (SAR) and summarises available protein-ligand activity data in the protein context. In this paper we describe the background that led to the development of both tools. We outline their implementation and describe their utility using in-house Structural Genomics Consortium (SGC) datasets and openly available data from the PDB and ChEMBL. Both tools are freely available to use and download at http://wonka.sgc.ox.ac.uk/WONKA/and http://oommppaa.sgc.ox.ac.uk/OOMMPPAA/.